Repeated stress gradually impairs auditory processing and perception. - Ghattas Bisharat; Ekaterina Kaganovski; Hila Sapir; Anita Temnogorod; Tal Levy; Jennifer Resnik (PLoS Biology)
Repetitive stress, a common feature of modern life, is a major risk factor for psychiatric and sensory disorders. Despite the prevalence of perceptual abnormalities in these disorders, little is known about how repetitive stress affects sensory processing and perception. Here, we combine repetitive stress in mice, longitudinal measurement of cortical activity, and auditory-guided behaviors to test if sound processing and perception of neutral sounds in adults are modulated by repetitive stress. We found that repetitive stress alters sound processing, increasing spontaneous cortical activity while dampening sound-evoked responses in pyramidal and PV cells and heightening sound-evoked responses in SST cells. These alterations in auditory processing culminated in perceptual shifts, particularly a reduction in loudness perception. Additionally, our work reveals that the impact of stress on perception evolves gradually as the stressor persists over time, emphasizing the dynamic and evolving nature of this mechanism. Our findings provide insight into a possible mechanism by which repetitive stress alters sensory processing and behavior, challenging the idea that stress primarily modulates emotionally charged stimuli.